2002
DOI: 10.1021/jo010983y
|View full text |Cite
|
Sign up to set email alerts
|

Highly Active, Air-Stable Palladium Catalysts for the C−C and C−S Bond-Forming Reactions of Vinyl and Aryl Chlorides:  Use of Commercially Available [(t-Bu)2P(OH)]2PdCl2, [(t-Bu)2P(OH)PdCl2]2, and [[(t-Bu)2PO···H···OP(t-Bu)2]PdCl]2 as Catalysts

Abstract: Air-stable palladium complexes [(t-Bu)(2)P(OH)](2)PdCl(2), [(t-Bu)(2)P(OH)PdCl(2)](2), and [[(t-Bu)(2)PO...H...OP((t-Bu)(2)]PdCl](2) serve as efficient catalysts for a variety of cross-coupling reactions of vinyl and aryl chlorides with arylboronic acids, arylzinc reagents, and thiols to yield the corresponding styrene derivatives, biaryls, and thioethers. (31)P NMR and mechanistic studies argue that the phosphinous acid ligands in the complexes can be deprotonated in the presence of a base to yield an electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(47 citation statements)
references
References 16 publications
2
45
0
Order By: Relevance
“…The dimerized title complex consists of a di-nuclear chlorido-bridged palladium entity consisting of hydrogen bridged through the oxygen atoms of the di-p-tolylphosphite groups on both phorsphorous atoms. The average O· · · O and P-O distances are 2.4057(27) Å and 1.546(2) Å respectively and are comparable to other similar compounds found in literature [7][8][9][10][11]. The asymmetric unit contains a monomer of the title complex while the other monomer is generated through the (1−x, 2−y, 1−z) symmetry.…”
Section: Discussionsupporting
confidence: 80%
“…The dimerized title complex consists of a di-nuclear chlorido-bridged palladium entity consisting of hydrogen bridged through the oxygen atoms of the di-p-tolylphosphite groups on both phorsphorous atoms. The average O· · · O and P-O distances are 2.4057(27) Å and 1.546(2) Å respectively and are comparable to other similar compounds found in literature [7][8][9][10][11]. The asymmetric unit contains a monomer of the title complex while the other monomer is generated through the (1−x, 2−y, 1−z) symmetry.…”
Section: Discussionsupporting
confidence: 80%
“…[19,20] Later on, these catalytic systems (11 or 12) have been also used for C À S coupling between thiols and vinyl halides, to afford vinyl thioethers (path B, Scheme 7). [21] An interesting approach for the synthesis of thioethers was developed by Sayah and Organ in which the Pd-PEPPSI IPent complex (13) catalyzed the CÀS coupling reaction at a comparatively lower temperature to provide the corresponding products in good to excellent yields. Some examples are presented in Scheme 8, path A.…”
Section: Palladiummentioning
confidence: 99%
“…[33] The authors have also studied the effect of various ligands and found that 22 was the best one for these transformations. The dithiocarbamates (21) were prepared through the reaction of 2-bromoaniline derivatives with CS 2 and triethylamine.…”
Section: Coppermentioning
confidence: 99%
“…We subsequently assessed the ability of dimer 3 to undergo direct reaction with an aryl iodide.T ot his end, we subjected [(PtBu 3 )Pd I (m-SEt)] 2 (3)to2equiv of 4-iodoaniline at 40 8 8Cf or 1h.W eo bserved clean formation of the corresponding SEt-functionalized aniline 4 in 84 %y ield relative to 2.0 equiv of ArI (see Scheme 1,bottom). Our 31 PNMR monitoring indicated that clean SEt/I exchange had taken place,w ith complete disappearance of dimer 3 and concomitant appearance of Pd I iodo dimer 1 (see the Supporting Information).…”
mentioning
confidence: 97%
“…Whereas palladium-catalyzed coupling reactions have developed into ubiquitous synthetic tools of significant industrial and societal impact, [1] thev ast majority of these coupling reactions rely on air-sensitive mononuclear Pd catalysts that are either used directly under inert conditions or formed in situ from suitable precursors. [1,2] As such, the recovery of the active Pd species is frequently challenging under routine laboratory conditions,u ltimately resulting in the disposal of the Pd. In this context, the emerging concept of dinuclear Pd I catalysis has shown promise in displaying features of air stability,r obustness,a nd recoverability in applications employing the iodine-bridged dinuclear Pd I complex 1 (Figure 1).…”
mentioning
confidence: 99%